"College for All? These Kids Can't Dig Ditches": Confronting the Leadership Challenges for Justice-Based Reform in Underperforming Schools. (March 2019) - Clemens, Randall F.
The case explores the challenges of school leaders to facilitate social justice–based reforms for low-income students of color who attend underperforming schools. In particular, it examines the 1st-year experiences of Principal Yolanda Lopez at Kennedy High School, an underperforming and underresourced urban public high school. Lopez is tasked with improving college access and readiness among all students. As the year progresses—and pressures mount from various stakeholders—she questions the viability of sustained reform and her own role as a change agent within a complex and often unjust system.